Interleukin-13 increases the stemness of limbal epithelial stem cells cultures - Trosan, Peter; Cabral, Joao Victor; Smeringaiova, Ingrida; Studeny, Pavel; Jirsova, Katerina (PloS one, 2022)
This study aimed to determine the effect of interleukin-13 (IL13) on the stemness, differentiation, proliferation, clonogenicity, and morphology of cultured limbal epithelial cells (LECs). Human limbal explants were used to culture LECs up to the second passage (P0-P2) with or without IL13 (IL13+ and IL13-, respectively). Cells were analyzed by qPCR (for the expression of ΔNp63α, BMI-1, keratin (K) 3, K7, K12, K14, K17, mucin 4, and MKI67) and immunofluorescence staining for p63α. The clonogenic ability was determined by colony-forming assay (CFA), and their metabolic activity was measured by WST-1 assay. The results of the CFA showed a significantly increased clonogenic ability in P1 and P2 cultures when LECs were cultured with IL13. In addition, the expression of putative stem cell markers (ΔNp63α, K14, and K17) was significantly higher in all IL13+ cultures compared to IL13-. Similarly, immunofluorescence analysis showed a significantly higher percentage of p63α positive cells in P2 cultures with IL13 than without it. LECs cultures without IL13 lost their cuboidal morphology with a high nucleocytoplasmic ratio after P1. The use of IL13 also led to significantly higher proliferation in P2, which can be reflected by a higher ability to reach confluence in P2 cultures. On the other hand, IL13 had no effect on corneal epithelial cell differentiation (K3 and K12 expression), and the expression of the conjunctival marker K7 significantly increased in all IL13+ cultures compared to the respective cell culture without IL13. This study showed that IL13 enhanced the stemness of LECs by increasing the clonogenicity and the expression of putative stem cell markers of LECs while maintaining their stem cell morphology. We established IL13 as a culture supplement for LESCs, which increases their stemness potential in culture, even after the second passage, and may lead to the greater success of LESCs transplantation in patients with LSCD.
Keywords: interleukin-13; Humans; Cell Differentiation; buněčná diferenciace; buněčné kultury; lidé; Cell Culture Techniques; Cells, Cultured; Epithelium, Corneal; Epithelial Cells; Interleukin-13; Stem Cells; kmenové buňky; Limbus Corneae; epitelové buňky; rohovkový epitel; kultivované buňky; limbus corneae